The Value of Pancasila as a Filter on Foreign Culture in the Era of the Information Technology (IT) Development Social Media - Anggit Wahyu Wijanarko (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
This research is motivated by the increasingly advanced technological developments, especially in terms of the use of social media. Social media in the era of advances in information technology allows us to more freely relate to people in various parts of the world. This can have both positive and negative impacts. One thing that needs to be addressed is the easier it is for foreign cultures to enter through social media which can affect national identity. Therefore, Pancasila as the nation's view of life means that Pancasila is the guideline for every behavior of the Indonesian nation. The values contained in Pancasila should be able to become a filter against incoming foreign cultures due to the easier access to social media in the current era of technological advancement. The formulation and purpose of this research is to provide a descriptive analysis of the application of Pancasila values as a filter against foreign cultures in the era of advances in social media information technology. The method used in this research is qualitative with a descriptive analysis approach. The data analysis technique used is content analysis. The benefits of this research are; 1) this research can be used as a reference for further similar studies, 2) this research can be used as an illustration of the application of Pancasila values in the filtering of foreign cultures in the era of advancing social media technology.